Consuming dividends - Konstantin Bräuer; Andreas Hackethal; Tobin Hanspal (Leibniz Institute for Financial Research SAFE, 2020)
This paper studies why investors buy dividend-paying assets and how they time their consumption accordingly. We combine administrative bank data linking customers' consumption transactions and income to detailed portfolio data and survey responses on financial behavior. We find that private consumption is excessively sensitive to dividend income. Investors across wealth, income, and age distributions increase spending precisely around days of dividend receipt. Importantly, the consumption response is driven by financially prudent investors who select dividend portfolios, anticipate dividend income, and plan consumption accordingly. Our results contribute to the literature on a dividend clientele and provide evidence of 'planned' excess sensitivity.
urn:nbn:de:hebis:30:3-534560
Keywords: G50; G40; G11; D12; D14; 330; Consumption; Stock market wealth; Dividends; Excess sensitivity; Self-control; Household finance; Retail investors